Controllable States and Porosity of Cu‐Carbon for CO2 Electroreduction to Hydrocarbons. Issue 37 (16th August 2022) - Wang, Jing; Chen, Yangshen; Zhang, Shishi; Yang, Chao; Zhang, Jun‐Ye; Su, Yaqiong; Zheng, Gengfeng; Fang, Xiaosheng
Abstract: The electrocatalytic carbon dioxide reduction reaction (CO2 RR) to value‐added chemical products is an effective strategy for both greenhouse effect mitigation and high‐density energy storage. However, controllable manipulation of the oxidation state and porous structure of Cu‐carbon based catalysts to achieve high selectivity and current density for a particular product remains very challenging. Herein, a strategy derived from Cu‐based metal‐organic frameworks (MOFs) for the synthesis of controllable oxidation states and porous structure of Cu‐carbon (Cu‐pC, Cu2 O‐pC, and Cu2 O/Cu‐pC) is demonstrated. By regulating oxygen partial pressure during the annealing process, the valence state of the Cu and mesoporous structures of surrounding carbon are changed, leads to the different selectivity of products. Cu2 O/CuO‐pC with the higher oxidation state exhibits FEC2H4 of 65.12% and a partial current density of −578 mA cm −2, while the Cu2 O‐pC shows the FECH4 over 55% and a partial current density exceeding −438 mA cm −2 . Experimental and theoretical studies indicate that porous carbon‐coated Cu2 O structures favor the CH4 pathway and inhibit the hydrogen evolution reaction. This work provides an effective strategy for exploring the influence of the various valence states of Cu and mesoporous carbon structures on the selectivity of CH4 and C2 H4 products in CO2 RR. Abstract : A controllable oxidation strategy derived from Cu‐based metal organic frameworks (MOFs) is introduced for the synthesis of controllable oxidation states and porous structure of Cu‐carbon (Cu‐pC, Cu2 O‐pC, and Cu2 O/Cu‐pC) for selective CO2 electroreduction. The Cu2 O/CuO‐pC with the higher oxidation state exhibits FEC2H4 of 65.12% and the Cu2 O‐pC shows the FECH4 over 55%.